Establishment of reference values of α-tocopherol in plasma, red blood cells and adipose tissue in healthy children to improve the management of chylomicron retention disease, a rare genetic hypocholesterolemia. Issue 1 (December 2016) - Cuerq, Charlotte; Restier, Lioara; Drai, Jocelyne; Blond, Emilie; Roux, Adeline; Charriere, Sybil; Michalski, Marie-Caroline; Di Filippo, Mathilde; Levy, Emile; Lachaux, Alain; Peretti, Noël
Abstract Background Chylomicron retention disease (CMRD), a rare genetic hypocholesterolemia, results in neuro-ophtalmologic damages, which can be prevented by high doses of vitamin E during infancy. In these patients, plasma vitamin E concentration is significantly reduced due to defects of chylomicron secretion. Vitamin E in adipose tissue (AT) and red blood cells (RBC) have been proposed as potential relevant biomarkers of vitamin E status but no reference values in children are available. The objectives were (i) to establish age-reference intervals in healthy children for α-tocopherol in plasma, red blood cells (RBC) and adipose tissue (AT) and (ii) to determine the variations of α-tocopherol in patients with CMRD after oral treatment with vitamin E. Methods This prospective study included 166 healthy children (1 month - 18 years) and 4 patients with CMRD. Blood and AT were collected in healthy children during a scheduled surgery and in patients before and after a 4-month treatment with α-tocopherol acetate. Results The reference ranges for α-tocopherol were 11.9 - 30 μmol/L in plasma, 2.0 - 7.8 μmol/L packed cells in RBC and 60 - 573 nmol/g in AT. α-tocopherol levels in plasma correlated with those of RBC (r = 0.31;p < 0.01). In patients with CMRD after 4 months treatment, α-tocopherol concentrations remained less than 70 % of the control values in plasma, increased by 180 % to reach normal values in RBC, and remained stable in the normal range in AT. Conclusion This study establishes pediatric reference intervals for α-tocopherol in plasma, RBC and AT. These values will be beneficial in assessing accurate α-tocopherol status in children and to optimize the monitoring of rare diseases such as CMRD. Our data suggest that RBC α-tocopherol, appears as a relevant biomarker to appreciate the effectiveness of treatment with α-tocopherol in patients with a rare primary hypocholesterolemia. The biopsy of AT could be used at diagnosis to assess the severity of the vitamin E deficiency and periodically after a long duration of vitamin E therapy to assess whether the treatment is effective, based on reference intervals defined in this study.